Mencegah Pemijahan Secara Tidak Terkontrol Dalam Pembesaran Ikan Nila Untuk Mempercepat Waktu Panen - Muhammad Safir; Novalina Serdiati; Nasmia Nasmia; Kasim Mansyur; Akbar Marzuki Tahya (Eumpang Breuh : Jurnal Pengabdian Masyarakat, 2023)
Nile tilapia (Oreochromis niloticus) is one of the freshwater fish commodities in Indonesia. In aquaculture, Nile tilapia often uncontrolled spawning, leading to inhibited growth, varied harvest sizes, and prolonged harvesting time to achieve the target production size of >250 g/fish. Application of sex reversal on larval stages (1-2 weeks old) and the sorting of Nile tilapia fingerlings (1-2 months old) are efforts that can be undertaken to address these issues. However, generally, the fish farming community in Tulo Rantea Village, Dolo District, Sigi Regency, Central Sulawesi Province, lacks a detailed understanding of the implementation of these technologies. The aim is to facilitate local community in applying the conveyed technology to contribute improvement of local economy. Simulation of the sex reversal method on larvae is conducted using a honey solution at a dosage of 10 mL/L of medium. Meanwhile, the sorting simulation employs a methylene blue solution. Implementation of these activities proceeds smoothly, and enthusiasm of community is notably high. In conclusion, the technology transfer, particularly in preventing uncontrolled spawning in Nile tilapia cultivation to expedite the harvest time, proves effective through simulation. This allows the community to easily understand and apply methods.